ANALISIS BATASAN USIA PERNIKAHAN DALAM HUKUM KELUARGA ISLAM PERBANDINGAN ANTAR NEGARA (Maladewa, Mesir, Pakistan dan Indonesia) - Itsnaini Firdausi Nuzulah Sholeh; Shofiatul Jannah (Hakam: Jurnal Kajian Hukum Islam dan Hukum Ekonomi Islam)
The procedure for implementing family law in countries with a majority Muslim population is different, this is influenced by variations in political structure, social structure, and cultural norms of each country. Different applications of family law in each country result in the determination of the minimum age of marriage varies also in each Islamic country. Islamic countries and Muslim-majority countries usually set the age of marriage between 15 and 21 years and usually Islamic countries distinguish age groups between men and women. Family law laws applicable in Pakistan, the Maldives, Egypt, and Indonesia are covered in this article. Using normative research methods, the authors highlight significant differences in setting the minimum age of marriage in each country. The age limit for marriage is compared to the applicable family laws in each country as part of the regulatory analysis. Analyze something compared using vertical, horizontal, and diagonal methods. The thought process of setting marriage age limits in each country is based on each madhhab that the country adheres to as well as the idea that social and cultural norms can be modified to fit the characteristics of that country. Although Islamic law provides freedom in setting a minimum age of marriage, each country has an important role in determining the legal age of marriage to protect its citizens.